Comparison of entropy measures in generalized maximum entropy estimation - Wilawan Srichaikul (2018)
© Published under licence by IOP Publishing Ltd. This study aims at comparing the efficiency of different Entropy measures in generalized maximum entropy estimation of the unknown parameters in macroeconomic panel data models by investigating the impacts of foreign direct investment on economic growth of 10 ASEAN countries over the period of 16 years (2001-2016). The three entropy measures (Shannon, Tsallis and Renyi entropy) are used as ordinary least squares estimator and generalized maximum entropy estimator. The results show that Tsallis entropy is the most appropriate to describe the effect of FDI on real GDP in ASEAN countries as it provides the maximum Max Entropy value and the lowest mean square error (MSE). The results of FDI indicates its positive impact on real GDP with the coefficient equal to 0.194 meaning when the FDI increases by 1 percent then the real GDP will increase by 0.194%. FDI is considered as one of the main factors affecting inward real GDP as an increase in production of goods and services leads to a rise in GDP This, in turn, makes the economy more attractive to the foreign investors.